The Influence And Strategy Of Ar-Rum Financing As Marketing In Improving Customer Micro Business At Pt. Pegadaian Syariah Unit Kejuruan Muda - Ruslan, Ruslan (Yayasan Adra Karima Hubbi, 2024)
Pegadaian Syariah is a system of guaranteeing debt with owned goods. Arrum Financing Products for Micro Businesses are a solution in getting additional business capital to develop their business. This study aims to analyze the influence of Arrum Financing and Marketing Strategy in Increasing Customer Micro Businesses at Pegadaian Syariah Vocational Unit Muda partially and simultaneously. The research method used is a quantitative method involving 86 respondents. Data collection through questionnaires, observations, and documentation were then analyzed using SPSS Version 25. The results of the study showed that partially Arrum Financing had a significant effect on Increasing Customer Micro Businesses with a sig value of 0.000 <? 0.01. Partially Marketing Strategy had a significant effect on Increasing Customer Micro Businesses with a sig value of 0.000 <? 0.01. Simultaneously, Arrum Financing and Marketing Strategy show that through the F test with a significant value of 0.000 which means it has a significant effect on Increasing Customer Micro Businesses.